2021
DOI: 10.1016/j.sjbs.2021.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of tobacco induces mitochondrial potential dependent cell death and epithelial-mesenchymal transition in gingival epithelial cells

Abstract: Smokeless tobacco habits are detrimental to oral health. A correlation between tobacco use and local epithelial tissue damage exists. Yet, the underlying cellular mechanism is not precisely characterized. This study assessed the dose-dependent action of Smokeless tobacco extract on gingival epithelial cells. Gingival tissue was taken from 5 healthy donors. Gingival epithelial cells were isolated by an enzymatic method and cultured up to passage 2. The cultured cells were treated with smokeless tobacco extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Changes in mitochondrial membrane potential (MMP) may evidence the organelle failure and lead to apoptosis [ 53 ]. We applied a permeable lipophilic fluorescent cationic dye DiIC1(5) as a marker of mitochondrial membrane depolarization (∆Ψm) [ 54 ]. Viable mitochondria with high membrane potential actively accumulated DiIC1(5), demonstrating a strong fluorescence, while in cells treated with XL-8 and XL-8-NPs mitochondria displayed dose-dependent fluorescence intensity decrease ( Figure 6 F).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in mitochondrial membrane potential (MMP) may evidence the organelle failure and lead to apoptosis [ 53 ]. We applied a permeable lipophilic fluorescent cationic dye DiIC1(5) as a marker of mitochondrial membrane depolarization (∆Ψm) [ 54 ]. Viable mitochondria with high membrane potential actively accumulated DiIC1(5), demonstrating a strong fluorescence, while in cells treated with XL-8 and XL-8-NPs mitochondria displayed dose-dependent fluorescence intensity decrease ( Figure 6 F).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the extracts with high Ni contents (exclude PAL ) only slightly exhibited DNA damage on HGEC ( Figures 2B , 5F , L , O ). These inconsistent results could be attributed to the differences in cellular physiology as well as the constituents of the exposure and exposed systems ( 46 , 47 ). As such, these comparisons further demonstrated that the cell apoptosis and DNA damages may not be correlated with the levels of heavy metal(loid)s in edible vegetables, but are also impacted by the other factors in each specific exposure scenario.…”
Section: Resultsmentioning
confidence: 99%
“…Volatile sulfur compounds and tobacco extract can induce mitochondrial MMP loss and apoptosis in GECs, leading to local epithelial damage [57,58]. The effect of cyclosporine A, an immunosuppressant that induces gingival hyperplasia, on GEC apoptosis is still debated.…”
Section: Gingival Epithelial Cellsmentioning
confidence: 99%